A study of the effect of densification and organic additives on the thermal behavior of pea husks - Bielecki, M.; Zubkowa, W.; Strojwas, A. (Національний технічний університет «Харківський політехнічний інститут», 2023)
It was stated that the compaction of a sample during its pyrolysis causes an almost two fold increase in content of hydrocarbons in the composition of volatile products in the temperature range of 350 - 470⁰C. Low density polyethylene (LDPE), novolac (NL), and coal pitch wastes (CTP) were added to feed stocks in the amount of 2 wt.% in order to decrease the contribution of saturated and unsaturated hydrocarbons along with oxygen-containing compounds in volatile products. The changes observed in the composition of volatile products were caused by the interaction of the material of additives with the inorganics present in the formed char.
Keywords: biomass; waste; interactions; biochar; біомаса; відходи; взаємодії; біовугілля